Monocyte chemoattractant protein 1, intercellular adhesion molecule 1, and vascular cell adhesion molecule 1 in exudative age-related macular degeneration - Jonas, Jost B.; Tao, Yong; Neumaier, Michael; Findeisen, Peter (Archives of ophthalmology, 2010)
To examine intraocular concentrations of monocyte chemoattractant protein 1 (MCP-1), soluble intercellular adhesion molecule 1 (sICAM-1), soluble vascular cell adhesion molecule 1 (sVCAM-1), and vascular endothelial growth factor (VEGF) in eyes with exudative age-related macular degeneration (AMD).The investigation included a study group of 28 patients (28 eyes) with exudative AMD and a control group of 25 patients (25 eyes) with cataract. The concentrations of MCP-1, sICAM-1, sVCAM-1, and VEGF in aqueous humor samples obtained during surgery were measured using a solid-phase chemiluminescence immunoassay.The study group as compared with the control group had higher aqueous concentrations of sICAM-1 (mean [SD], 844 [2073] vs 246 [206] pg/mL, respectively; P < .001), sVCAM-1 (mean [SD], 7978 [7120] vs 2999 [1426] pg/mL, respectively; P < .001), and MCP-1 (mean [SD], 587 [338] vs 435 [221] pg/mL, respectively; P = .07). The concentration of VEGF did not vary significantly between the groups (P = .76). The MCP-1 concentration was significantly associated with macular thickness (r = 0.40; P = .004). It decreased significantly with the type of subfoveal neovascular membrane (classic membrane type, occult membrane, retinal pigment epithelium detachment) (P = .009). The concentrations of sICAM-1, sVCAM-1, and VEGF were not significantly associated with membrane type and macular thickness (P ≥ .18).Concentrations of MCP-1, sICAM-1, and sVCAM-1 are significantly associated with exudative AMD, even in the presence of normal VEGF concentrations. Intraocular MCP-1 concentrations are correlated with the subfoveal neovascular membrane type and the amount of macular edema. One may infer that MCP-1, sICAM-1, and sVCAM-1 could potentially be additional target molecules in therapy for exudative AMD.Arch Ophthalmol. 2010;128(10):1281-1286-->